Indebtedness in Brazil: mapping from the data analysis bootcamp promoted by Enap - Gonçalves Fonseca Moura, Bruna; Rezende Lopes, Érika; Batista Monteiro, Grace; Kaltenecker Retto de Queiroz, Iluska (Revista del CLAD Reforma y Democracia, 2025)
This project, developed as the final part of the Data Analysis Bootcamp for Women at the National School of Public Administration (Enap), provides a comprehensive overview of the indebtedness of the Brazilian population. Based on the knowledge acquired during the bootcamp, it was possible to extract, clean, and analyze data from the Central Bank of Brazil on this topic using the Python language. The tools and techniques learned allowed the creation of graphic and interactive visualizations, providing a clear and informative analysis of the current scenario of indebtedness in the country. The article discusses how indebtedness varies among different population groups, reflecting their distinct economic realities. The analysis reveals that the forms and reasons for indebtedness differ significantly according to individuals’ occupation and income. These findings are crucial for the formulation of more effective public policies that consider the specificities of each group and aim to mitigate the risks associated with excessive indebtedness of Brazilian families.
Keywords: Economic Analysis of Indebtedness; Consumer Credit; Financial Inclusion; Default; Public Policies for Indebtedness